Pengaruh Keadilan Distributif dan Keadilan Prosedural Terhadap Keterikatan Karyawan dengan Persepsi Dukungan Organisasi sebagai Variabel Mediasi PT Ramayana Plaza Andalas Kota Padang Tahun 2022 - Tafonao, Sukadamai; Jhon Rinaldo; Susi Yuliastanty (Fakultas Ekonomi, Universitas Ekasaktii, 2023)
Work engagement has always been an important issue in the world of work, this is closely related to the quality of Human Resources which will then determine the success and progress of a company. The purpose of the study was to determine the effect of distribution and justice procedures on employee engagement with perceived organizational support as a mediating variable at PT Ramayana Plaza Andalas, Padang City in 2022. The data collection methods were field research and library research. Types and sources of data are primary data and secondary data. The population of this study were all employees of the Ramayana Plaza Andalas Company, Padang City, amounting to 150 people and a sample of 60 people. The analysis method uses path analysis. The results of the study are: (1) distributive justice and procedural justice variables together have a significant effect on employee engagement at PT Ramayana Plaza Andalas, (2) directly distributive justice has a significant effect on perceptions of organizational support for PT Ramayana Plaza Andalas. (3) direct procedural justice has a significant effect on organizational support for PT Ramayana Plaza Andalas, (4) directly distributive justice has a significant effect on employee engagement at PT Ramayana Plaza Andalas. (5) directly procedural justice has a significant effect on employee engagement at PT Ramayana Plaza Andalas, (6) directly perceived organizational support has a significant effect on employee engagement at PT Ramayana Plaza Andalas. (7) there is an effect of distributive justice on employee engagement through perceived organizational support, (8) there is an effect of procedural justice on employee engagement through perceived organizational support.